Effects of two different half-squat training programs on fatigue during repeated cycling sprints in soccer players - Bogdanis, G. C.; Papaspyrou, A.; Souglis, A. G.; Theos, A.; Sotiropoulos, A.; Maridaki, M. (The Journal of Strength and Conditioning Research, 2011)
This study compared the effects of two different half-squat training programs on the repeated-sprint ability of soccer players during the preseason. Twenty male professional soccer players were divided into 2 groups: One group (S-group) performed 4 sets of 5 repetitions with 90% of their 1-repetition maximum (1RM), and the other group (H-group) performed 4 sets of 12 repetitions with 70% of 1RM, 3 times per week for 6 weeks, in addition to their common preseason training program. Repeated-sprint ability was assessed before and after training by 10 × 6-second cycle ergometer sprints separated by 24 seconds of passive recovery. Maximal half-squat strength increased significantly in both groups (p < 0.01), but this increase was significantly greater in the S-group compared with the H-group (17.3 ± 1.9 vs. 11.0 ± 1.9%, p < 0.05). Lean leg volume (LLV) increased only in the H-group. Total work over the 10 sprints improved in both groups after training, but this increase was significantly greater in the second half (8.9 ± 2.6%) compared with the first half of the sprint test (3.2 ± 1.7%) only in the S-group. Mean power output (MPO) expressed per liter of LLV was better maintained during the last 6 sprints posttraining only in the S-group, whereas there was no change in MPO per LLV in the H-group over the 10 sprints. These results suggest that resistance training with high loads is superior to a moderate-load program, because it increases strength without a change in muscle mass and also results in a greater improvement in repeated sprint ability. Therefore, resistance training with high loads may be preferable when the aim is to improve maximal strength and fatigue during sprinting in professional soccer players.